2015
DOI: 10.5114/jcb.2015.52127
|View full text |Cite
|
Sign up to set email alerts
|

Original paper Evaluation of the dosimetric impact of loss and displacement of seeds in prostate low-dose-rate brachytherapy

Abstract: PurposeTo analyze the seed loss and displacement and their dosimetric impact in prostate low-dose-rate (LDR) brachytherapy while utilizing the combination of loose and stranded seeds.Material and methodsTwo hundred and seventeen prostate cancer patients have been treated with LDR brachytherapy. Loose seeds were implanted in the prostate center and stranded seeds in the periphery of the gland. Patients were imaged with transrectal ultrasound before implant and with computerized tomography/magnetic resonance ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Wang et al . [ 32 ] reported that the prostate post-implant V 100 , D 90 , and rectal wall RV 100 for patients without seed loss were 94.6%, 113.9%, and 0.98 cm 3 , respectively, as compared to 95.0%, 114.8%, and 0.95 cm 3 for the group with seed loss; there were no correlations between seed loss due to migration and post-plan dosimetry. Miyazawa et al .…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al . [ 32 ] reported that the prostate post-implant V 100 , D 90 , and rectal wall RV 100 for patients without seed loss were 94.6%, 113.9%, and 0.98 cm 3 , respectively, as compared to 95.0%, 114.8%, and 0.95 cm 3 for the group with seed loss; there were no correlations between seed loss due to migration and post-plan dosimetry. Miyazawa et al .…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al . reported that it had no impact on the implant quality of initial whole prostate LDR brachytherapy [ 22 ]. However, in focal partial re-implantation, it is necessary to avoid seed migration to maintain implant quality.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, local movement of seeds with the prostate might affect the sectoral dose, whereas dosimetry of the whole prostate might be unaffected. Clinical results have not yet been able to implicate these local migrations to a reduced possibility for cure 72 . Distant migration of seeds to lungs or other vital organs can cause temporary self‐limiting side‐effects, such as bloody sputum, pneumorrhagia, pneumothorax, and also late sequelae, including secondary cancers 73,74 …”
Section: Resultsmentioning
confidence: 99%